Biographical dictionary of anthropologists - Stewart, William 1927- (McFarland, 2009)
"This biographical dictionary provides information on 322 men and women who have made significant contributions in the field of anthropology. Arranged alphabetically, each entry includes a short biography, a detailed analysis of the theories or approaches that each contributed to his or her field, and the person's major works of literature"--Provided by publisher.